Metabolomics reveals differences of metal toxicity in cultures of Pseudomonas pseudoalcaligenes KF707 grown on different carbon sources - Booth, Sean C.; Weljie, Aalim M.; Turner, Raymond J. (Frontiers in Microbiology, 2015)
Co-contamination of metals and organic pollutants is a global problem as metals interfere with the metabolism of complex organics by bacteria. Based on a prior observation that metal tolerance was altered by the sole carbon source being used for growth, we sought to understand how metal toxicity specifically affects bacteria using an organic pollutant as their sole carbon source. To this end metabolomics was used to compare cultures of Pseudomonas pseudoalcaligenes KF707 grown on either biphenyl or succinate as the sole carbon source in the presence of either aluminum or copper. Using multivariate statistical analysis it was found that the metals caused perturbations to more cellular processes in the cultures grown on biphenyl than those grown on succinate. Aluminum induced many changes that were indicative of increased oxidative stress as metabolites involved in DNA damage and protection, the Krebs cycle and anti-oxidant production were altered. Copper also caused metabolic changes that were indicative of similar stress, as well as appearing to disrupt other key enzymes such as fumarase. Additionally, both metals caused the accumulation of biphenyl degradation intermediates indicating that they interfered with biphenyl metabolism. Together these results provide a basic understanding of how metal toxicity specifically affects bacteria at a biochemical level during the degradation of an organic pollutant and implicate the catabolism of this carbon source as a major factor that exacerbates metal toxicity.